2015
DOI: 10.1016/j.neuron.2014.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Il10 Deficiency Rebalances Innate Immunity to Mitigate Alzheimer-Like Pathology

Abstract: SUMMARY The impact of inflammation suppressor pathways on Alzheimer’s disease (AD) evolution remains poorly understood. Human evidence suggests involvement of the cardinal anti-inflammatory cytokine, interleukin-10 (Il10). We crossed the APP/PS1 mouse model of cerebral amyloidosis with a mouse deficient in Il10 (APP/PS1+Il10−/−). Quantitative in silico 3D modeling revealed activated Aβ phagocytic microglia in APP/PS1+Il10−/− mice that restricted cerebral amyloidosis. Genome-wide RNA sequencing of APP/PS1+Il10−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
279
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(308 citation statements)
references
References 79 publications
15
279
3
Order By: Relevance
“…However, although microglia can phagocytose and digest aggregated Aβ in a lysosome-dependent manner (22,62,63), our data indicate that they contributed only a small part to the steady-state pool of PGRN and lysosomes around amyloid plaques. Our results do not rule out physiologically important roles for microglia and their lysosomes in β-amyloid metabolism, as proposed by recent studies (64)(65)(66). However, we establish that the majority of the PGRN that accumulates at amyloid plaques is axonal.…”
Section: Discussioncontrasting
confidence: 84%
“…However, although microglia can phagocytose and digest aggregated Aβ in a lysosome-dependent manner (22,62,63), our data indicate that they contributed only a small part to the steady-state pool of PGRN and lysosomes around amyloid plaques. Our results do not rule out physiologically important roles for microglia and their lysosomes in β-amyloid metabolism, as proposed by recent studies (64)(65)(66). However, we establish that the majority of the PGRN that accumulates at amyloid plaques is axonal.…”
Section: Discussioncontrasting
confidence: 84%
“…Aβ plaques were quantified using the Surfaces function followed by volume analysis in IMARIS software (Bitplane). IMARIS-based quantification of microglial number, morphology, and Aβ phagocytosis followed previously described methods using the Colocalization and Surfaces functions (28)(29)(30)33). To calculate Aβ internalization ratio, the volume of Aβ within CD68 + phagolysosomes was normalized to microglia number and total Aβ volume within the field.…”
Section: Methodsmentioning
confidence: 99%
“…3K). In addition to traditional proinflammatory cytokines, two recent studies demonstrated that the antiinflammatory cytokine interleukin 10 (IL-10) negatively regulates amyloid pathology (27,28). We therefore also examined levels of IL-10 in all four groups.…”
Section: Microglial Activation and Phagocytosis Is Altered In Rag-5xfadmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the outcomes have been mixed for other preclinical models. In differing mouse models of Alzheimer's disease, viral mediated overexpression of IL-10 worsens amyloid-β plaque deposition, while IL-10 deficiency promotes amyloid-β plaque clearance and improved outcomes on cognitive tasks (Chakrabarty et al, 2015;Guillot-Sestier et al, 2015). In contrast, intracerebroventricular infusions of IL-10 receptor blocking antibodies exacerbates disease onset in the SOD1 G93A model of ALS, while targeted intrathecal overexpression of IL-10 in CD11b-expressing microglial cells greatly improves disease progression (Gravel et al, 2016).…”
Section: Future Research Directions and Clinical Implicationsmentioning
confidence: 99%